When I think of Christmas [compact disc] - Grant, Amy; Gill, Vince (MCA Nashville, 2024)
A new compilation of Christmas songs from Amy Grant and Vince Gill's career. It includes the brand new song, "When I Think of Christmas,' that Amy recorded for this album, as well as the duet of "'Til The Season Comes Around Again," that is performed during their Ryman Residency each year.